Direction-sensitive dark matter search with the low-background gaseous detector NEWAGE-0.3b". (29th April 2021) - Ikeda, Tomonori; Nakamura, Kiseki; Shimada, Takuya; Yakabe, Ryota; Hashimoto, Takashi; Ishiura, Hirohisa; Nakamura, Takuma; Ito, Hiroshi; Ichimura, Koichi; Abe, Ko; Kobayashi, Kazuyoshi; Tanimori, Toru; et al.
Abstract: NEWAGE is a direction-sensitive dark matter search using a low-pressure gaseous time projection chamber. A low alpha-ray emission rate micro pixel chamber had been developed in order to reduce background for dark matter search. We conducted the dark matter search at the Kamioka Observatory in 2018. The total live time was 107.6 d, corresponding to an exposure of 1.1 kg\> d. Two events remained in the energy region of 50–60 keV, which was consistent with the expected background of 2.5 events. A directional analysis was carried out and no significant forward–backward asymmetry derived from the WIMP-nucleus elastic scatterings was found. Thus a 90% confidence level upper limit on the spin-dependent WIMP-proton cross-section of 50 pb for a WIMP mass of 100 GeV\>c^-2 was derived. This limit is the most stringent yet obtained from direction-sensitive dark matter search experiments.